2020
DOI: 10.3390/rs12244062
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Copernicus Sea Level Altimetry Products in the Baltic Sea and Estonian Lakes

Abstract: Multi-mission satellite altimetry (e.g., ERS, Envisat, TOPEX/Poseidon, Jason) data have enabled a synoptic-scale view of ocean variations in past decades. Since 2016, the Sentinel-3 mission has provided better spatial and temporal sampling compared to its predecessors. The Sentinel-3 Ku/C Radar Altimeter (SRAL) is one of the synthetic aperture radar altimeters (SAR Altimeter) which is more precise for coastal and lake observations. The article studies the performance of the Sentinel-3 Level-2 sea level altimet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The dense network of in situ tide gauges in the Baltic Sea also supports satellite altimetry studies because tide gauges data allow for efficient validation of satellite altimetry data; for example, as a result of the validation of the Sentinel-3A and Sentinel-3B Level-2 altimetry products along the Estonian coast. Liibusk et al [50] found that satellite altimetry can determine the height of the sea level in Estonian coastal areas with an average accuracy of 80 ± 70 mm. Sentinel-3 Level-2 sea level altimetry products and 2019 data were used in this study.…”
Section: Satellite Altimetrymentioning
confidence: 99%
“…The dense network of in situ tide gauges in the Baltic Sea also supports satellite altimetry studies because tide gauges data allow for efficient validation of satellite altimetry data; for example, as a result of the validation of the Sentinel-3A and Sentinel-3B Level-2 altimetry products along the Estonian coast. Liibusk et al [50] found that satellite altimetry can determine the height of the sea level in Estonian coastal areas with an average accuracy of 80 ± 70 mm. Sentinel-3 Level-2 sea level altimetry products and 2019 data were used in this study.…”
Section: Satellite Altimetrymentioning
confidence: 99%
“…This is the direct product recorded by the satellite altimetry. The SSH values are provided along the satellites' ground tracks or at regular grids interpolated from the values determined along the satellite tracks, e.g., the Copernicus Marine Environment Monitoring Service provides regular and systematic reference information (data products) on the physical and biogeochemical ocean and sea ice state for the global ocean and European regional seas [50].…”
Section: Monitoring Sea-level Rise For Coastal Resiliencementioning
confidence: 99%
“…The SSH values are provided along the satellites' ground tracks or at regular grids interpolated from the values determined along the satellite tracks, e.g., the Copernicus Marine Environment Monitoring Service (CMEMS) provides regular and systematic reference information (data products) on the physical and biogeochemical ocean and sea ice state for the global ocean and the European regional seas. The CMEMS is implemented and operated by Mercator Ocean, which provides oceanographic products and services for maritime safety, coastal and marine environment, climate and weather forecasting, and marine resource users [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…This is the direct product of satellite altimetry. Additionally, the SSH values are provided along the satellites' ground tracks or at regular grids interpolated from the values determined along the satellite tracks, e.g., CMEMS provides regular and systematic reference information on the physical and biogeochemical ocean and sea ice state for the global ocean and the European regional seas [38,39]. Here, we used a "GLOBAL_REANALYSIS_PHY_001_030" reanalysis data product to obtain global sea surface high monthly grid data with a data resolution of 5' covering the period 1993 to 2019 (26 years in total).…”
Section: Introductionmentioning
confidence: 99%